Local Community Synergy in Cultural Tourism Management : Realizing Environmental Sustainability in Tourism Villages - Deby Eprilianto; Suci Megawati; Yuyun Eka Kartika Sari; Eni Febriyanti; Lisa Amelia Sari; Mohammad Hermy H. (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
The Nyanggring cultural tourism village in Tlemang Village, Lamongan, is a local wisdom-based tourism development initiative with a focus on environmental sustainability. Synergy between local communities and managers is key to creating this sustainability. However, challenges in implementing environmentally friendly management and actively involving the community are still faced. This study uses a qualitative approach with in-depth interview techniques and participatory observation. Research informants consisted of local communities, tourism village managers, and policy makers. Data were analyzed using thematic analysis techniques to identify supporting and inhibiting factors in sustainability-based cultural tourism management. The findings show that collaboration between the community and managers in preserving culture and the environment is very significant. The community is involved in maintaining cultural sites, managing cultural tourism villages, and developing local tourism products. However, there are still challenges such as lack of capacity training and minimal incentives for communities who are active in management. The synergy between the local community and the Nyanggring tourism village managers in Tlemang Village has made a positive contribution to environmental sustainability, but requires more support in terms of training and policies to optimize the results.